Community empowerment in increasing screening coverage for cervical cancer prevention at the Jatilawang Community Health Center - Didik Setiawan; Sarwito Rachmad Barmawi; Githa Fungie Galistiani (Community Empowerment, 2023)
Cervical cancer ranks among the most common gynecological cancers globally. The collaborative community service with the Jatilawang Community Health Center aims to provide early detection facilities for cervical cancer, with the expectation of reducing the percentage of cervical cancer infections in the Jatilawang District. The community empowerment model, focused on enhancing screening coverage for cervical cancer prevention at the Jatilawang Community Health Center, was implemented through outreach activities held on March 9 and 16, 2023. The activities targeted both husbands and wives, utilizing booklet media. This program successfully increased knowledge and interest among the residents of Jatilawang District in cervical cancer screening for prevention purposes.